Inbound marketing : get found using Google, social media and blogs - Halligan, Brian, 1967- (The new rules of social media, 2010)
Stop pushing your message out and start pulling your customers in Traditional "outbound" marketing methods like cold-calling, email blasts, advertising, and direct mail are increasingly less effective. People are getting better at blocking these interruptions out using Caller ID, spam protection, TiVo, etc. People are now increasingly turning to Google, social media, and blogs to find products and services. Inbound Marketing helps you take advantage of this change by showing you how to get found by customers online. Inbound Marketing is a how-to guide to getting found via Google, the blogosphere, and social media sites. - Improve your rankings in Google to get more traffic - Build and promote a blog for your business - Grow and nurture a community in Facebook, LinkedIn, Twitter, etc. - Measure what matters and do more of what works online The rules of marketing have changed, and your business can benefit from this change. Inbound Marketing shows you how to get found by more prospects already looking for what you have to sell.